2021
DOI: 10.1186/s41938-021-00378-6
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of entomopathogenic fungi and botanicals against sucking pests of okra: an ecofriendly approach

Abstract: Background Okra, Abelmoschus esculentus (Linn.) Moench, is one of the most important traditional vegetables in India. The crop is attacked severely by sucking pests, viz., jassid, Amrasca biguttula biguttula Ishida, and whitefly, Bemisia tabaci Genn., throughout its growth period. To control these sucking pests, different entomopathogenic fungi (EPF), viz., Beauveria bassiana, Metarhizium anisopliae, and Lecanicillium lecanii were tested alone and their 1:1 combinations with neem oil against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Interestingly, the integration of IPM components with B. bassiana AAUMB-29 showed a control index value of 100% followed by B. bassiana AAUMB-29 + Hunter 40 EC (90%). is result was similar to the finding that showed the integrated application of L. lecanii (2 × 10 9 spores/ml) with neem oil (0.5%) recorded the higher whitefly population reduction (71.57%) on Okra [60,64] and the combined application of B. bassiana (1 × 10 9 spores/ml) with half-field recommended doses of spinosad (0.25 ml/l) caused up to 89.35% reduction of whitefly populations over control treatments from cucumber [65] under field conditions. e field study also revealed that combined spray application of entomopathogenic fungi B. bassiana and M. anisopliae with a sublethal dose of neem oil (0.5%) and Hunter 40 EC (1.25 ml/L) achieved 0.98 to 1.24-fold higher whitefly population reduction compared to single treatment applications.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the integration of IPM components with B. bassiana AAUMB-29 showed a control index value of 100% followed by B. bassiana AAUMB-29 + Hunter 40 EC (90%). is result was similar to the finding that showed the integrated application of L. lecanii (2 × 10 9 spores/ml) with neem oil (0.5%) recorded the higher whitefly population reduction (71.57%) on Okra [60,64] and the combined application of B. bassiana (1 × 10 9 spores/ml) with half-field recommended doses of spinosad (0.25 ml/l) caused up to 89.35% reduction of whitefly populations over control treatments from cucumber [65] under field conditions. e field study also revealed that combined spray application of entomopathogenic fungi B. bassiana and M. anisopliae with a sublethal dose of neem oil (0.5%) and Hunter 40 EC (1.25 ml/L) achieved 0.98 to 1.24-fold higher whitefly population reduction compared to single treatment applications.…”
Section: Discussionsupporting
confidence: 89%
“…From the result, the combination of entomopathogenic fungi and A. indica extract showed promising results against nymphs and adult aphids. Similarly, the coapplication of entomopathogenic fungi and A. indica extract showed effective pesticidal activities and may become an effective component of insect pest management programs against various insect pests [48]. In this study, about 75% of nymph and adult aphids were killed by coapplication of the products.…”
Section: Coapplication Of Entomopathogenic Fungal Isolates Withmentioning
confidence: 64%
“…We observed that the combination of plant extracts with entomopathogenic fungi significantly increased the mortality rates. Similarly, previous studies showed that the coapplication of plant extracts and entomopathogenic fungi significantly increased the mortality of several insect pests compared to individual application of plant extracts or entomopathogenic fungi [24,[46][47][48]. As explained by [49], A. indica products can be mixed with other bioproducts or with synergists to increase their efficacy due to the unique mode of action derivatives interfering with the hormonal system of insects.…”
Section: Coapplication Of Entomopathogenic Fungal Isolates Withmentioning
confidence: 94%
See 1 more Smart Citation
“…Sulfoxaflor inhibit and play an important role in interactions with nicotinic acetylcholine receptors (nAChR) of insect. The mixture of insecticides becomes more useful for applying a way for toxicity and mortality of various pests and reducing insect population (Liguori et al, 2010 andHalder et al, 2021). Under laboratory study, the used Uphold 36% SC (Spinetoram 6% + Methoxyfenozide 30%), when different instars E. insulana larvae were exposed and feeding, observed to stop feeding immediately and notice that time taken 3 to 5 days to kill the pest, (Kandil et al, 2022).…”
mentioning
confidence: 99%